DEVELOPMENT OF A DEEP LEARNING BASED E-MODULE INTEGRATED WITH UNIVERSAL DESIGN FOR LEARNING (UDL) ON THE RESPIRATORY SYSTEM - Andi papada; Adnan; Faisal; Firdaus Daud; Muhiddin Palennari (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2026)
The rapid advancement of education has led to a shift toward more flexible and student-centered learning. However, instructional materials used in schools are still largely conventional and lack interactivity, which may reduce student engagement and limit conceptual understanding. Therefore, integrating deep learning approaches with Universal Design for Learning (UDL) principles into digital teaching materials is considered important to promote meaningful and inclusive learning. This study focuses on developing an e-module on the respiratory system based on a deep learning approach integrated with UDL principles, as well as evaluating its validity, practicality, and effectiveness. This research adopts a research and development (R&D) approach using the ADDIE model. The study was conducted at SMAN 6 Sinjai, involving 30 students as participants. Data were collected through expert validation sheets, practicality questionnaires completed by teachers and students, and learning outcome tests. Data analysis was carried out using Aiken’s V to assess validity, percentage analysis to evaluate practicality, and N-Gain to measure effectiveness. The developed e-module incorporates meaningful, conscious, and enjoyable learning activities, contextual problem-solving tasks, and multiple forms of representation, engagement, and expression to accommodate diverse learners. The results show that the e-module has high validity, is practical for classroom implementation, and is effective in improving students’ conceptual understanding, as indicated by the N-Gain results. These findings imply that the developed e-module can facilitate more meaningful, inclusive, and effective biology learning, particularly in enhancing students’ understanding of the respiratory system.